Death by Suicide—The EMS Profession Compared to the General Public. (4th May 2019) - Vigil, Neil H.; Grant, Andrew R.; Perez, Octavio; Blust, Robyn N.; Chikani, Vatsal; Vadeboncoeur, Tyler F.; Spaite, Daniel W.; Bobrow, Bentley J.
Abstract: Background: In 2016, nearly 45, 000 deaths in the United States were attributed to suicide making this the 10th leading cause of death for all ages. National survey data suggest that among Emergency Medical Technicians (EMTs), including firefighters and Paramedics, rates of suicide are significantly higher than among the general public. EMTs face high levels of acute and chronic stress as well as high rates of depression and substance abuse, which increase their risk of suicide. Objective/Aim: To determine the statewide Mortality Odds Ratio (MOR) of suicide completion among EMTs as compared to non-EMTs in Arizona. Methods: We analyzed the Arizona Vital Statistics Information Management System Electronic Death Registry of all adult (≥18) deaths between January 1, 2009 and December 31, 2015. Manual review of decedent occupation was performed to identify the EMT cohort; all other deaths were included in the non-EMT cohort. Using the underlying cause of death as the outcome, we calculated the MOR of both the EMT and non-EMT cohorts. Results: There were a total of 350, 998 deaths during the study period with 7, 838 categorized as suicide. The proportion of deaths attributed to suicide among EMTs was 5.2% (63 of 1, 205 total deaths) while the percentage among non-EMTs was 2.2% (7, 775/349, 793) (p < 0.0001). The crude Mortality Odds Ratio for EMTs compared with non-EMTs was [cMOR 2.43; 95% CI (1.88–3.13)]. After adjusting for gender, age, race, and ethnicity, EMTs had higher odds that their death was by suicide than non-EMTs [aMOR: 1.39; 95% CI (1.06–1.82)]. Conclusion: In this statewide analysis, we found that EMTs had a significantly higher Mortality Odds Ratio due to suicide compared to non-EMTs. Further research is necessary to identify the underlying causes of suicide among EMTs and to develop effective prevention strategies.